How do Women Maintain Access to Land in the Context of Multiple Land Users in Contemporary Rural Tanzania? - Mbezi, Rose; Mwaipopo, Rosemarie (Tanzania Journal of Sociology, 2025)
Rural Tanzania is increasingly experiencing a growing heterogeneity of land users, driven by demographic shifts, socio-economic changes, and policy transformations, all of which influence women's ability to maintain secure access to land. Customary practices such as marriage, inheritance, and communal property access are now being practiced alongside statutory frameworks, including land policies and the transformation of communal land into private property, often influenced by economic investments and land acquisitions. Although legislative frameworks have been established to facilitate land access for both men and women, they remain insufficient, as women continue to face challenges in sustaining access to land amidst the emergence of multiple land users with multiple land use systems. Guided by Marxist Feminist (MF) and Feminist Political Ecology (FPE) theories, this study employed a qualitative research approach to examine women's experiences in accessing land in Mohoro East and Mohoro West villages in Rufiji District, Tanzania. The findings reveal that social transformation is reshaping the cultural meanings attached to land resulting to multiple process sometimes challenging women’s ability to maintain access to land. Nonetheless, some women are actively exercising their agency by adopting context-specific strategies to reclaim and maintain access to land. These insights highlight the need for a more nuanced discourse on women's capacity to retain land access in contemporary rural settings, ensuring their effective use of land to support food security in rural communities